2022
DOI: 10.3390/ph15050535
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anticancer Activity of Hymenocardia acida Stem Bark Extract Loaded into PLGA Nanoparticles

Abstract: Hymenocardia acida (H. acida) is an African well-known shrub recognized for numerous medicinal properties, including its cancer management potential. The advent of nanotechnology in delivering bioactive medicinal plant extract with poor solubility has improved the drug delivery system, for a better therapeutic value of several drugs from natural origins. This study aimed to evaluate the anticancer properties of H. acida using human lung (H460), breast (MCF-7), and colon (HCT 116) cancer cell lines as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…In our previous work, we have demonstrated that the leaf extract of A. Africana efficiently induces apoptotic cell death in breast, colon, pancreatic, and leukemic cancer cell lines in a dose-dependent manner [20]. Cytotoxic activity of the ethanolic extract of H. Acida stem bark in human breast (MCF-7) and colon (HCT 116) cell lines was also reported by Adedokun et al [21].…”
Section: Pro-apoptotic Effectssupporting
confidence: 62%
“…In our previous work, we have demonstrated that the leaf extract of A. Africana efficiently induces apoptotic cell death in breast, colon, pancreatic, and leukemic cancer cell lines in a dose-dependent manner [20]. Cytotoxic activity of the ethanolic extract of H. Acida stem bark in human breast (MCF-7) and colon (HCT 116) cell lines was also reported by Adedokun et al [21].…”
Section: Pro-apoptotic Effectssupporting
confidence: 62%
“…As shown in the figure, both NPs ( Figs. 3A and 3B ) were spherical morphology with a homogeneous distribution were produced ( Adedokun et al, 2022 ; Malewicz et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of the OAE–PLGA NPs was demonstrated using FE-SEM (Apreo 2; Thermo Scientific, Waltham, MA, USA) ( Adedokun et al, 2022 ). The sample containing OAE–PLGA NPs were dispersed in distilled water and placed in an ultrasonic bath for 45 min to sonicate.…”
Section: Methodsmentioning
confidence: 99%
“…To address these concerns and adhere to the principles of green chemistry, the biosynthesis of AgNPs has gained prominence due to its simplicity, eco-friendly nature, and cost-effectiveness. Furthermore, AgNPs synthesized through biological methods exhibit desirable properties, such as high-water solubility, biocompatibility, and reduced toxicity [ 26 ]. However, compared to chemical approaches, biological processes generally have slower reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%